Opportunities for Reproductive Health Programs in the Implementation of Schools Re-Entry Policy on Teenage Pregnancy and Sexually Transmitted Infections: Case of Selected Urban Schools in Kenya - Kijungu, Kishasha; Thumbi, Samuel; Orago, Alloys; Wagoro, Miriam (Journal of Health, Medicine and Nursing, 2024)
Purpose: This study was designed to determine the opportunities available for the ministry of health as the custodian of reproductive health programs on mitigating teenage pregnancy and sexually transmitted infections in Kenya. Methodology: This was an analytical cross-sectional study that triangulated various sampling techniques. Based on unmitigated increase number of school pregnancies and sexually transmitted infections, the study obtained information on opportunities available to introduce and implement reproductive health program from the specialists in the ministries of health and education using Focus Group Discussions, Key Informant interviews and questionnaires techniques. A total of 16 respondents was realized using the standard saturation point method. Multistage followed by cluster sampling techniques were used to identify selected urban towns. A sample size of 174 school-female teenage participants female were tested for pregnancy and sexually transmitted infections in the eight urban areas. Analysis of data was done by use of descriptive statistics, Analysis of Variance (ANOVA) and content analysis. Findings: The study found out that the ministry of health through the National Sexual and Reproductive Health Policy and its strategic plans had not taken up the opportunity to perform its role of supporting re-entry policy and reproductive health education in schools. Although the Ministry of health, through its established organs had a role to play in mitigating Teenage Pregnancy and Sexually Transmitted infections, it had not put structures in place for its implementation in schools. Unique contribution to Theory, practice and Policy: The ministry of health needs to support school-entry policy as part of its mandate. Successful programs and policies require the involvement of all stakeholders in designing, developing and implementing and must be inclusive and well resource supported. The findings of this study need to be appraised by the policy makers and implementers for fresh and improved interventions.